Study of some physiological , productive and microbial parameters of goat kids feed kefir milk - Tabarek K. Al-Ghazi; Meitham K, AL-Galiby (University of Thi-Qar Journal of agricultural research, 2021)
This study was conducted in the animal farm of the College of Agriculture and Marshes / University of Dhi Qar for the period from 6/11/2020 to 16/2/2021 to study the effect of using different levels of kefir milk on the performance of local goats kids. The study included (16) local males kids of Iraqi Local goats. And the experiment lasted 100 days. Introductory 16 day of adapt .The goats were taken after weaning at the age of 3-4 months with an average weight of (19.59 ± 2.81) kg. They were purchased from the local markets and were examined by the veterinarian to ensure their safety and free from diseases. The goats were randomly divided into four groups with four kids for each group. The feed was provided as 3% of the live body weight. The quantities of feed provided were adjusted every two weeks based on the new mean weight of each group. The experimental animals were randomly divided into four treatments